Answer:
$3,000
Step-by-step explanation:
There two possible outcomes:
There is a 3/4 chance that the bid is rejected for a value of -$1,400
There is a 1/4 chance that the bid is accepted for a value of $17,600 - $1,400.
The expected value of the situation is:
![E = \frac{3}{4}*(-1,400)+\frac{1}{4}*(17,600-1,400)\\E=\$3,000](https://tex.z-dn.net/?f=E%20%3D%20%5Cfrac%7B3%7D%7B4%7D%2A%28-1%2C400%29%2B%5Cfrac%7B1%7D%7B4%7D%2A%2817%2C600-1%2C400%29%5C%5CE%3D%5C%243%2C000)
The expected value is $3,000.
Answer : 4 times
Here it's given that ,
- The height and base of the butterfly sitting on the stem (red butterfly) is two times greater than the height and base of the butterfly sitting on the flower .
And we need to find out how many times the area of red winged butterfly is greater than that of sitting on the flower (blue butterfly) .
Let us take ,
- base of blue butterfly be b
- height of blue butterfly be h
- Area be A .
Then ,
- base of red butterfly will be 2b .
- height of red butterfly will be 2h .
- Area be A' .
We know that ,
→ area of the triangle = 1/2 × base × height
So that ,
→ A/A' = (1/2 * b * h) ÷ (1/2 *2b *2h)
→ A/A' = bh/4bh
→ A/A' = 1/4
→ A' = 4A
<u>Henceforth</u><u> the</u><u> area</u><u> of</u><u> </u><u>blue</u><u> butterfly</u><u> is</u><u> </u><u>4</u><u> </u><u>times </u><u>greater</u><u> than</u><u> </u><u>that</u><u> of</u><u> </u><u>red </u><u>winged</u><u> butterfly</u><u> </u><u>.</u>
I hope this helps.
The equation in the form of the given expression is (0)² + (1)² = 1
<h3>Trigonometry identity</h3>
According to some of the trigonometry identity
sin 0 = 0
cos 0 1
Given the expression below
sin^2 0+cos^2 0=1
This can also be expressed as:
(sin0)² + (cos0)² = 1
Substitute
(0)² + (1)² = 1
Hence the equation in the form of the given expression is (0)² + (1)² = 1
Learn more on trig identity here: brainly.com/question/20094605
#SPJ1
8m+27= 2m-3
take 2m and subtract it from 8m, this gives you 6m. now your equation is 6m+27=-3.
subtract 27 from -3, this will make it 6m=-30.
divide 30 by 6. this gives you your answer. m=-5, because -30 divided by 6 equals -5.
now to test it you can plug -5 into the equation in place of M. 8 times -5 equals -40, plus 27 equals -13. 2 times -5 equals -10 plus -3 equals -13.
Answer:
A
Step-by-step explanation:
18 + 12 = 30
A: 6 (3 + 2) = 30
Simplified 6*5 = 30